2005
DOI: 10.1055/s-2004-826189
|View full text |Cite
|
Sign up to set email alerts
|

Biliopleural Fistula as a Late Complication of Percutaneous Transhepatic Cholangioscopy

Abstract: References1 Carrasco CH, Zornoza J, Bechtel WJ. Malignant biliary obstruction: complica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Percutaneous transhepatic biliary drainage is often used in treatment of obstructive biliary disease to relieve symptoms prior to surgery or palliatively in patients who are poor candidates for surgery [ 1 ]. Biliopleural fistula is a rare complication following this procedure, which may be due to the passage of catheter through the pleural cavity before crossing the diaphragm and into the bile duct when a transhepatic approach is used [ 1 , 5 - 7 ]. Elevated pressure gradient in the biliary tract could drive the bile leak back into the pleural cavity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Percutaneous transhepatic biliary drainage is often used in treatment of obstructive biliary disease to relieve symptoms prior to surgery or palliatively in patients who are poor candidates for surgery [ 1 ]. Biliopleural fistula is a rare complication following this procedure, which may be due to the passage of catheter through the pleural cavity before crossing the diaphragm and into the bile duct when a transhepatic approach is used [ 1 , 5 - 7 ]. Elevated pressure gradient in the biliary tract could drive the bile leak back into the pleural cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that fistula formation occurs within 3 weeks of catheter placement and biliopleural effusion may develop when the catheter remained in bile duct for more than 4 weeks [ 1 ]. One study revealed common features that lead to the development of the BF: (i) Complete biliary obstruction was present; (ii) Catheter placement was between the 9th and 10th ribs in the midaxillary line; (iii) prolonged drainage (7 days to 2 months) preceded fistula formation [ 7 ]. These features are also seen in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, endoscopic cholangioscopy is less invasive and does not carry the theoretical risk of tumour seeding that potentially occurs in percutaneous cholangioscopy 70 . It also avoids the formation of a permanent biliary fistula 77 when a PTC drains an obstructed segment from above. Potential complications of endoscopic drainage include cholangitis as a result of contamination of a partially drained system – mandating prophylactic antibiotics 70 – and the standards risks of endoscopy.…”
Section: Endoscopymentioning
confidence: 99%